Inventory of Anura In The Sarasah Uwak Waterfall Area of Padang City West Sumatra - Imam Wahyudi; Fitra Nugraha (Jurnal Serambi Biologi, 2023)
The Tourist area of Sarasah Uwak Waterfall is an area that the general public is starting to look at as a tourist location, but there is no data related to the diversity of Anura species in this area. Research was conducted in November 2022. Sample collection was carried out using the Method Visual Encounter Survey. A total of six species, six genera consisting of 2 families, namely Ranidae and Dicroglossidae. The Ranidae family has the most number of species with four species, namely: Odorrana hosii, Indosylvirana nicobariensis, Chalcorana parvaccola, Chalcorana parvacola, and Hylarana erythraea, followed by the Dicroglossidae with two species, namely: Limnonectes blythii and Occidozyga sumatrana